Results of a convex-back cemented keeled glenoid component in primary osteoarthritis: multicenter study with a follow-up greater than 5 years - Walch, Gilles; Young, Allan A.; Melis, Barbara; Gazielly, Dominique; Loew, Markus; Boileau, Pascal (Journal of shoulder and elbow surgery, 2011)
Purpose - We assessed the clinical and radiologic results of a cemented all-polyethylene convex-back keeled glenoid component used with a third-generation prosthesis. - Methods - Between 1996 and 2003, in 4 European centers, 333 shoulder arthroplasties were performed for primary osteoarthritis by use of a cemented all-polyethylene convex-back keeled glenoid component. Kaplan-Meier survivorship analysis was performed, and clinical outcome was assessed with the Constant score, range of motion, and subjective evaluation. - Results - At a mean of 89.5 months’ follow-up, the Constant score improved from 31.4 to 67.6 points (P < .0001). Active forward elevation improved from 94.9° to 146.6° (P < .0001) and external rotation from 9.0° to 35.3° (P < .0001). Of the patients, 93.5% were either satisfied or very satisfied. The rate of revision for glenoid loosening was 0.6%; however, the rate of radiologic glenoid loosening was 18.9%. Glenoid survival was 99.7% at 5 years and 98.3% at 10 years with endpoint defined as revision surgery for glenoid loosening and 99.7% at 5 years and 51.5% at 10 years with endpoint defined as radiologic loosening. - Conclusions - We showed highly satisfactory clinical outcomes and extremely low rates of revision for glenoid loosening using a cemented convex-back keeled glenoid. There was a concerning rate of radiologic loosening, which only became apparent after 5 years, and this was associated with excessive glenoid reaming. Because radiologic changes are progressive and precede the need for revision, innovations in this field need to report radiologic and clinical results with follow-up of at least 5 to 10 years to prove any superiority.
Online verfügbar 5 November 2010
Gesehen am 04.11.2022